Using sport for corporate social responsibility (CSR) in Finland - Hakala, Antti (2015)
Companies are increasingly valued beyond their capability to maximize profits. Responsibility is one of the core issues in companies’ strategies nowadays. Meanwhile sport and health professionals are facing challenges: inactivity among people and costs in grassroots participation are growing. Therefore, the relationship between sport and business around the phenomenon called corporate social responsibility (CSR) has grown in importance.